PENINGKATAN KETERAMPILAN PEMBUATAN CURRICULUM VITAE DAN PERSIAPAN WAWANCARA KERJA DALAM MENGHADAPI DUNIA KERJA 5.0 - Nurul Giswi Karomah; Dudi Haryadi; Bakri Bakri; Umi Hanik Makmuroh; Enggun Gunawan (POLITEKNIK LP3I JAKARTA, 2023)
After completing formal education, a person has the hope of getting a job and starting a career. A high school graduate, diploma or bachelor of course also wants to earn their own income or find a job. Therefore, new graduates need to have a strategy so that they can be looked at by companies or employers. Both strategies in making Curriculum Vitae and preparing for job interviews. Seeing this, the Jakarta LP3I Polytechnic together with PT SOS, which is a higher education partner, held training in the form of community service activities in order to improve CV writing skills and interview preparation for prospective employees of PT SOS. The purpose of this training is to meet the information and knowledge needs of PT S.O.S prospective employees in preparing documents and job interviews. Provision of making a Curriculum Vitae and interview preparation for prospective job candidates at PT SOS is expected to have self-branding, recognize each other's weaknesses and strengths, be able to write them in the Curriculum Vitae and be able to present them during interviews. The method provided is by delivering material in the form of seminars and direct assistance in making CVs and practicing job interviews. The result of this service activity is that after participating in the training, participants are expected to be proficient in making a Curriculum Vitae as a provision for applying for jobs to be able to promote themselves and provide information about their abilities so as to give a strong impression in the eyes of recruiters and are ready to undergo a job interview session.Key words: Training, Development, Curriculum Vitae, Job Interview